Janice Guy - Struth, Thomas 1954- (Hunters Point Press, 2018)
This is the first monograph on British-born photographer Janice Guy (born 1953), gathering her radical experiments in photography from the late 1970s. Made while she was a student at the Kunstakademie Düsseldorf, this selection of photographs sheds light on Guy's work as an artist before she gained international renown as a gallerist of contemporary art. The German photographer Thomas Struth, a fellow student in Germany at the time, has written a moving essay for this book about their formative years and ongoing friendship. The book also includes an introduction by American photographer Justine Kurland, which makes a compelling case for the reconsideration of these photographs today. The work presented in Janice Guy, much of which appears here for the first time, reverberates as never before amid the current proclivity for producing and circulating images of ourselves
Keywords: Guy, Janice -- 1953-; Aktfotografie; Guy, Janice 1953-; Photography of the nude; Bildband